Education for Sustainable Development: Exploring Sustainability Learning and Praxis in Higher Management Education - A Case Study of the Graduate School of Business in Trinidad and Tobago - Heeralal, Cindy (2011)
In this dissertation, the author conducts an exploratory case study analysis of the integration of sustainability in higher education at the Arthur Lok Jack Graduate School of Business in Trinidad and Tobago. The study utilizes a multi-method research approach to qualitative data collection where data was derived from two main sources: interviews with specific faculty and staff were conducted as well as a survey instrument was administered to MBA/Finance cohorts. Semi-structured interviews were carried out with faculty in an attempt to gain perspectives from the management of the Business School on the process of integration of sustainability and social responsibility and inclusion into the School activities, the status of sustainability teaching and practice and the challenges faced during these processes. A survey was administered to students to assess the perception, awareness and extent of visibility of sustainability in teaching and practice at the Business School. Additional research was conducted using a document analysis methodology in examining communications and messages from the institution. Furthermore, the study also adopts a reflexive methodology as the author is a former employee and associate of the institution.